The Female Holiness. The Case of Teresa de Jesús - García-Hernán, Enrique (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
This note presents an assessment of the book: Teresa de Jesús: La construcción de la santidad femenina. This book deals with the historiographical debate in recent years about female holiness (religious model) in the Spanish Baroque era. It uses the case of Teresa de Jesús as a success in achieving holiness.
Keywords: Teresa de Jesús; female holiness; hispanic monarchy; spiritual movements